Menopause and the Menstrual Equity Agenda - Weiss-Wolf, Jennifer (Columbia Journal of Gender and Law, 2021)
I was in fifth grade, the year 1978, and the weathered purple- and orange-covered paperback copy of Are You There God? It’s Me, Margaret. was finally mine to check out of the school library for an entire week. I read it cover to cover that first night, and surely a dozen times over in the years that followed. I have since reflected upon the extraordinary gifts Judy Blume bestowed in Margaret: enabling children to be seen, respected, and met right when and where it mattered. She validated the most mundane, yet oddly prolific, questions about periods that were clearly on the minds of many. Four decades later, it is fair to say that the most meaningful moments of my legal career have been spent considering the very same topic—menstruation—in a quest to ensure its political centrality to issues of social justice, democratic participation, and gender equality. For my own part, commitment to menstrual equity has entailed examining our current laws and systems to see where discrimination and bias exist and persist—from public benefits to tax codes to education—and then forging the arguments to reverse that. And then, importantly, reimagining, crafting, and advancing new and more equitable policies in their place.